Complex network evolution of the key coastal ports in China under the Belt and Road Initiative. (8th November 2022) - Xu, Xu; Yang, Yanbin; Liu, Yi; Liu, Wei; Li, Yan
In order to promote the construction of 'The Belt and Road' Initiative, we construct the complex network evolution model based on the complex network theory and node attractiveness. We select the relevant 2017 data of 18 coastal ports mentioned in the Belt and Road Initiative, and verify the validity of the model by comparing the network eigenvalues between evolving network and real network. The results show that the average distances between ports are short, clustering coefficient and dependence of hub ports are high, its topological structure has scale-free network characteristics and fits the power law distribution. Meanwhile, we study the change of network characteristics of the evolutionary network and real network under deliberate attack and random attack. The statistics show that the robustness is weak under deliberate attack but strong under random attack. These are great reference to the construction and development of China's Belt and Road Initiative.